Nerve growth factor modulates information processing in the auditory thalamus - Villa, A; Bajo Lorenzana, V; Vantini, G (Elsevier, 1999)
The spatio-temporal organization of spike discharges was studied in rat auditory thalamus (i.e., medial geniculate body and auditory sector of thalamic reticular nucleus) following a 2-week continuous intracerebroventricular administration of nerve growth factor (NGF). Recording of extracellular single-unit activity indicated that, in medial geniculate body, NGF induced a significant increase of the mean firing rate. In thalamic reticular nucleus, where units tend to discharge in bursts, NGF increased the average burst size (number of spikes) and the intraburst frequency without affecting the firing rate. Following white noise acoustical stimulation, in medial geniculate body, more onset excitation and a lower signal-to-noise ratio were observed in NGF-treated rats than in controls. Conversely, in thalamic reticular nucleus, NGF-treated animals showed more inhibitory responses than controls. In addition, within the medial geniculate body, functional interactions between pairs of units simultaneously recorded from different electrodes were greatly increased by the nerve growth factor treatment. These data indicate that modifications of temporal pattern of discharges in selected brain regions are among the effects induced by the intracerebroventricular administration of nerve growth factor.